1998
DOI: 10.1182/blood.v92.7.2527.2527_2527_2534
|View full text |Cite
|
Sign up to set email alerts
|

Early Phagocytosis of Glucose-6-Phosphate Dehydrogenase (G6PD)-Deficient Erythrocytes Parasitized by Plasmodium falciparum May Explain Malaria Protection in G6PD Deficiency

Abstract: In population-based studies it has been established that inherited deficiency of erythrocyte (E) glucose-6-phosphate dehydrogenase (G6PD) confers protection against severe Plasmodium falciparum (P falciparum) malaria. Impaired growth of parasites in G6PD-deficient E in vitro has been reported in some studies, but not in others. In a systematic analysis, we have found that with five different strains ofP falciparum (FCR-3, KI, C10, HB3B, and T9/96), there was no significant difference in either invasion or matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 35 publications
3
69
0
5
Order By: Relevance
“…La coincidencia geográfica mencionada apoya la teoría de que la malaria es un factor selectivo respecto a la presencia de defectos eritrocíticos. En el caso específico de la deficiencia de G6PD, las mujeres heterocigotas portadoras de esta deficiencia podrían estar protegidas contra la malaria causada por Plasmodium falciparum y las hemoglobinopatías confieren algún grado de protección contra la malaria grave por P. falciparum (4,6,7). Algunos estudios realizados en poblaciones africanas han mostrado una menor densidad de la parasitemia, que pareciera indicadora de esa protección o resistencia (8)(9)(10), mientras que otros parecen indicar que los defectos eritrocíticos innatos no confieren protección contra la malaria (11).…”
Section: Forma De Citarunclassified
“…La coincidencia geográfica mencionada apoya la teoría de que la malaria es un factor selectivo respecto a la presencia de defectos eritrocíticos. En el caso específico de la deficiencia de G6PD, las mujeres heterocigotas portadoras de esta deficiencia podrían estar protegidas contra la malaria causada por Plasmodium falciparum y las hemoglobinopatías confieren algún grado de protección contra la malaria grave por P. falciparum (4,6,7). Algunos estudios realizados en poblaciones africanas han mostrado una menor densidad de la parasitemia, que pareciera indicadora de esa protección o resistencia (8)(9)(10), mientras que otros parecen indicar que los defectos eritrocíticos innatos no confieren protección contra la malaria (11).…”
Section: Forma De Citarunclassified
“…In a previous study in Burkina Faso, Ouattara et al (2014) showed that G6PD deficiency protect against asymptomatic malaria [15]. The same result was found in Gabon [26,25]. In a systematic review, [27] it was mentioned that that G6PD deficiency can potentially protect against uncomplicated malaria in African countries, but not severe malaria [27].…”
Section: The Impact Of G6pd Deficiency and Hemoglobin Genotypes On Pmentioning
confidence: 70%
“…Impaired growth of parasites in G6PD-deficient erythrocyte in vitro has been reported in some studies, but not in others. In a rprevious report, Marina Cappadoro et al, 1998, it was showed that G6PD deficient erythrocyte parasitized were phagocytosed 2.3 times more intensely than normal [25]. In a previous study in Burkina Faso, Ouattara et al (2014) showed that G6PD deficiency protect against asymptomatic malaria [15].…”
Section: The Impact Of G6pd Deficiency and Hemoglobin Genotypes On Pmentioning
confidence: 99%
“…Desidrogenase de Glicose-6-fosfato (G6PD) -Para seu desenvolvimento, o parasita aumenta consideravelmente sua necessidade metabólica, num período limitado de tempo, gerando um estresse adicional à célula hospedeira, levando-a à destruição. A membrana eritrocitária sofre modificações decorrentes desses processos oxidantes, levando a uma fagocitose acentuada dos eritrócitos em indivíduos thalassêmicos, com traço falcêmico e com deficiência em G6PD (Cappadoro et al, 1992). O gene da G6PD é ligado ao cromossomo X e apresenta numerosas mutações, que causam deficiência enzimática nos eritrócitos.…”
Section: Fatores Genéticos Humanos Relacionados Com a Susceptibilidadunclassified